Asymmetry, but where? Terms of address in pet-, infant-, and child-directed speech in Turkish - Ketrez, F. Nihan (Taikomoji kalbotyra, 2023)
Terms of address in Turkish spontaneous pet-, infant-, and child-directed speech were compared in terms of the proportion of diminutive and hypocoristic morphemes attached to various types of bases. The goal of the study was to see whether there was any difference in their distribution in different addressee groups that could be attributed to the asymmetrical communication in pet-directed speech. The results showed that, in Turkish, a language poor in diminutives and hypocoristics, the asymmetry is not observed in the distribution of diminutive and hypocoristic forms. It is observed, however, in the morphopragmatic expression of endearment in general that included the possessive morphology, which seemed to be an alternative form used instead of diminutives and hypocoristics or along with them.